Cediranib or placebo in combination with cisplatin and gemcitabine chemotherapy for patients with advanced biliary tract cancer (ABC-03): a randomised phase 2 trial. Issue 8 (August 2015) - Valle, Juan W; Wasan, Harpreet; Lopes, Andre; Backen, Alison C; Palmer, Daniel H; Morris, Karen; Duggan, Marian; Cunningham, David; Anthoney, D Alan; Corrie, Pippa; Madhusudan, Srinivasan; Maraveyas, Anthony; et al.
Summary: Background: Cisplatin and gemcitabine is the standard first-line chemotherapy regimen for patients with advanced biliary tract cancer; expression of VEGF and its receptors is associated with adverse outcomes. We aimed to assess the effect of the addition of cediranib (an oral inhibitor of VEGF receptor 1, 2, and 3) to cisplatin and gemcitabine on progression-free survival. Methods: In this multicentre, placebo-controlled, randomised phase 2 study, we recruited patients aged 18 years or older with histologically confirmed or cytologically confirmed advanced biliary tract cancer from hepatobiliary oncology referral centres in the UK. Patients were eligible if they had an ECOG performance status of 0–1 and an estimated life expectancy of longer than 3 months. Patients were given first-line cisplatin and gemcitabine chemotherapy (25 mg/m 2 cisplatin and 1000 mg/m 2 gemcitabine [on days 1 and 8 every 21 days, for up to eight cycles]) with either 20 mg oral cediranib or placebo once a day until disease progression. We randomly assigned patients (1:1) with a minimisation algorithm, incorporating the stratification factors: extent of disease, primary disease site, previous treatment, ECOG performance status, and centre. The primary endpoint was progression-free survival in the intention-to-treat population. This study is registered withClinicalTrials.gov, numberNCT00939848, and was closed on Sept 30, 2014; results of the final analysis for the primary endpoint are presented. Findings: Between April 5, 2011, and Sept 28, 2012, we enrolled 124 patients (62 in each group). With a median follow-up of 12·2 months (IQR 7·3–18·5), median progression-free survival was 8·0 months (95% CI 6·5–9·3) in the cediranib group and 7·4 months (5·7–8·5) in the placebo group (HR 0·93, 80% CI 0·74–1·19, 95% CI 0·65–1·35; p=0·72). Patients who received cediranib had more grade 3–4 toxic effects than did patients who received placebo: hypertension (23 [37%] vs 13 [21%]; p=0·05), diarrhoea (eight [13%] vs two [3%]; p=0·05); platelet count decreased (ten [16%] vs four [6%]; p=0·09), white blood cell decreased (15 [24%] vs seven [11%]; p=0·06) and fatigue (16 [24%] vs seven [11%]; p=0·04). Interpretation: Cediranib did not improve the progression-free survival of patients with advanced biliary tract cancer in combination with cisplatin and gemcitabine, which remains the standard of care. Although patients in the cediranib group had more adverse events, we recorded no unexpected toxic effects. The role of VEGF inhibition in addition to chemotherapy for patients with advanced biliary tract cancer remains investigational. Funding: Cancer Research UK and AstraZeneca Pharmaceuticals.